Answer:
x = 3 and y = 1
Explanation:
Lets name the first equation as equation 1.
[Equation 1] x + y = 3
Then name the second equation as equation 2.
[Equation 2] x - 2y = 0
The first purpose is to eliminate one of the variable. In this case, it looks like it is easier to eliminate x since both equations have single x.
We will use [Equation 1] - [Equation 2] to eliminate x and find the value of y.
(x + y) - (x - 2y) = 3 - 0
x + y - x + 2y = 3
3y = 3
y = 1
Now that we know y = 1, we will substitute this value into any of the two equations to find the value of x. Here, I choose to substitute into [equation 1].
x + y = 3
x + 1 = 3
x = 2
So now we found out that x = 2 and y = 1.